Semen Parameters of Fertile Men Attending Tribhuvan University Teaching Hospital - Lamichhane, B; Baral, J R; Manandhar, R; Shrestha, A (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to analyze the semen parameters of fertile Nepalese men with a known time to pregnancy of less than or equal to 12 months and to compare the values obtained with the newer reference limit of WHO, 2010. Methods: A hospital based prospective cross- sectional study was conducted at Tribhuvan University Teaching Hospital, Institute of Medicine, from 15th April 2012 – 15th April 2013. Sixty fertile men with a known time to pregnancy (TTP) ≤ 12 months were included in the study and semen collection and analysis done at the laboratory of Department of Pathology. Results: The following one-sided reference limits, the fifth centile (with 95th percent confidence interval), were generated: semen volume, 1.0 ml (0.8-1.2); total sperm number, 25 million per ejaculate (11-39); sperm concentration, 10 million per ml (5-15); progressive motility, 15% (10-20); total (progressive plus non-progressive motility) motility, 30% (25 -35); vitality 50% (46-54); morphologically normal form, 99% (99.3- 99.4). Conclusions: The study concluded that only a single semen parameter cannot be conclusive of fertility, therefore combination of all semen parameters is more predictive. In addition the study also concluded that the semen parameters of Nepalese fertile men were found lower as compared to reference limits of WHO. DOI: http://dx.doi.org/10.3126/njog.v9i2.11772